Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Answer:
= -10
Step-by-step explanation:
p + (-q) - 2 = x
if:
p = -3
q = 5
then:
-3 + (-5) - 2 = x
we know that:
+(-) = -
then:
-3 +(-5) - 2 = -3 - 5 - 2 = x
x = -10
The value of the expression p + (-q) - 2 is -10 if the p = -3 and q = 5 the answer is -10.
What is an expression?
It is defined as the combination of constants and variables with mathematical operators.
We have given an expression:
= P + (-q) - 2
Plug p = -3
q = 5
= -3 + (-5) - 2
= -3 - 5 - 2
= -10
Thus, the value of the expression p + (-q) - 2 is -10 if the p = -3 and q = 5 the answer is -10.
Learn more about the expression here:
brainly.com/question/14083225
#SPJ1
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.